PENGELOLAAN LIMBAH PERTANIAN SEBAGAI SUMBER ENERGI TERBARUKAN - Loso Judijanto; Al-Amin (CV. Adiba Aisha Amira, 2025)
The management of agricultural waste as a renewable energy source offers an innovative approach to addressing environmental issues and the growing demand for energy. Agricultural waste, such as straw, husks, and livestock manure, has the potential to be processed into biogas, bioethanol, and biomass using various technologies such as anaerobic digesters and pyrolysis. This utilization not only reduces greenhouse gas emissions but also optimises underutilised resources. In addition to providing added value to the agricultural sector, the energy produced reduces dependence on fossil fuels and generates organic fertilisers that improve soil quality. Thus, the management of agricultural waste as a renewable energy source provides significant economic and environmental benefits and contributes to sustainable energy development.